Relationship Between Shyness and Generalized Pathological Internet Use Among Chinese School Students: The Serial Mediating Roles of Loneliness, Depression, and Self-Esteem - Gao, Fengqiang; Guo, Zongxin; Tian, Yu; Si, Yingdong; Wang, Peng (Frontiers in Psychology, 2018)
The present study aimed to explore the mediating effects of loneliness, depression, and self-esteem on the relationship between shyness and generalised pathological Internet use (GPIU). A total of 5,215 school students completed questionnaires regarding shyness, loneliness, depression, self-esteem, and GPIU. The self-reported scores for GPIU, shyness, loneliness, depression, and self-esteem were tested in students from elementary schools to universities. The results of a variance analysis indicated that senior high school students had the greatest prevalence of GPIU of all of the study stages. With the study stages resolved, the results of a structural equation model (SEM) revealed that: (a) shyness positively predicted GPIU; (b) shyness/loneliness/depression predicted GPIU through self-esteem; (c) shyness predicted GPIU though loneliness/depression → self-esteem; and (d) shyness predicted GPIU though loneliness → depression → self-esteem. Overall, these findings provide important implications for the prevention and intervention of GPIU in Chinese school students.